Socio-Economic Determinants of Child Marriage: Evidence from the Iranian Provinces - Mozhgan Asna-ashary; Mohammad Reza Farzanegan; Mehdi Feizi; Hassan F. Gholipour (Center for Economic Studies and ifo Institute (CESifo), 2020)
We study the socio-economic determinants of child (girls below age of 19 years) marriage using a panel data of thirty Iranian provinces from 2007 to 2015. Our panel fixed effects and generalized method of moments (GMM) estimations show that the level of income per capita (with negative effect), inflation and income inequality (both with positive effect) are the significant determinants of child marriage. Our results which control for province fixed effects (e.g. local cultural norms or geographical conditions) do not show a significant effect of religiosity captured by a household's spending on religious products and services. To reduce child marriage, which has long-run negative effects on the development of children, policymakers need to focus on economic issues and distribution of income, thus reducing the economic incentives or necessities of families to accept the practice of child marriage. Child marriage is more rooted in economic deprivation than in religiosity of households.
Keywords: J12; J13; P46; 330; child marriage; Iran; poverty; panel regression